THE POLEMOGENIC WAVE OF REVOLUTIONS 1917-1927 AS A HISTORICAL LABORATORY - Nikolai Sergeyevich Rozov (Сравнительная политика, 2017)
Abstract. The main link between revolutions in a polemogenic wave is participation of correspondent states in a common war (Πόλεμος — war,  Γέννηση — birth). The polemogenic wave caused by the First World War includes successful revolutions (with the change of power) in Russia, Germany, Hungary, the success of some national liberation movements of Irish people, Czechs, Slovaks, South Slavs, Poles, Finns, the defeat of such movements of Ukrainians, Georgians, Armenians, peoples of Turkestan, the establishment of regimes of various types and with different stability. The article presents an approach to identify causes of different types of dynamics and the consequences of revolutionary events in within the wave. The approach includes comparisons using methods of similarity and difference, as well as the application of binarization and Boolean algebra according to Ch. Ragin's method. The application of this approach makes it possible to put forward hypotheses about causes and patterns of revolutionary dynamics and consequences in the polemogenic wave: what determines inclusion of a society into the wave, the level of loyalty of ethnic provinces in relation to their empire, success and failure of revolutions, existence and absence of civil war, relationship between revolution and religion, nature and fate of the cultural avant-garde.